The examination of poultry feather digestility for biogas production - Mézes, Lili; Bíró, Tibor; Tamás, János; Petis, Mihály (Acta Agraria Debreceniensis, 2007)
The aim of this research was the elaboration of the technological parameters of biological digestion and biogas production from poultry feather produced in large quantities by slaughterhouses. Feather protein was digested by Bacillus licheniformis, keratin desintegrator bacteria. Investigations focused on the optimalization of parameters influencing poultry feather biodegradation. The optimal range of pH, temperature, feather size and bacillus:feather ratio were determined in the experiments as well as the analysis of relationship between the examined parameters. In order to be able to track the dinamics of the biodegradation, we determined the extintion level of the liquid phase of the biodegraded material in the different experimental treatments. The results showed that the rate of hydrolisis was significantly higher in the treatments with bacteria than in the treatments without it. The most extensive digestion were observed in case of 1:3 feather:water ratio. The highest intensity of feather digestion were detected in the treatment with 1% microbe ratio.